Factors Influencing TVET Teacher’s TPACK Competencies - Salleh, Mohammad Hafiz; Suhaida Abdul Kadir; Rahimah Jamaluddin; Mohd Hazwan Mohd Puad (Journal of Technical Education and Training, 2022)
Developing competent teachers is one of the main focuses of national TVET’s transformation. The teaching profession demands that teachers constantly strive to improve the quality of their professionalism to become competent and quality teachers. In addition, TVET teachers must be prepared to withstand the technological boom in the industrial revolution 4.0 digital era to keep them in line with 21st-century learning. Thus, the Technological Pedagogical Content Knowledge (TPACK) framework is designed to meet the competencies that TVET teachers need. The primary purpose of this study was to assess the factors that influence the TPACK competency of TVET Teachers. Furthermore, to determine the relationship between mentoring role, school environment, and TVET teacher’s competencies. A total of 400 TVET teachers from two categories of TVET-related institutions under the Malaysian Education TVET division were selected as the study’s sample: vocational education upper secondary stream (PVMA) from National Secondary School (SS) and Vocational College (VC). Data were analyzed using a t-test, correlation, and multiple linear regression. The findings revealed significant differences in the level of technological knowledge competency between the two school categories. The role of mentoring and the school environment is also significantly related to the TPACK competency of TVET teachers. Meanwhile, the school environment predicts a change in the TPACK teachers’ competency for TVET teachers in Peninsular Malaysia. Therefore, the study discovers the role of the mentoring role and the school environment in determining new factors influencing TVET teachers’ TPACK competency. For further research, it is recommended to study the mentoring role in mediating the relationship between the school environment and TVET teachers’ TPACK competency.